Seasonal variations of physical and blood profiles, nutrition and eating attitude in high school rhythmic gymnastic athletes - Ishigaki, T.; Koyama, K.; Kaya, M.; Nakamura, M.; Tsujita, J.; Hori, S. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The investigation was an attempt to examine the seasonal changes in physical and blood profiles, nutrition and eating attitude in high school rhythmic athlete at on- and off-season. Findings: The changes in physical profiles indicated increases of muscle and bone mass. Hence, post-season is important period of physical development. It was strange phenomenon that plasma leptin concentration was increased almost 50% with unchanged body fat percentage. It was likely that regular menstrual cycle have need of muscle mass and leptin.